2014
DOI: 10.1136/jnnp-2014-308232
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anxiety on verbal and visuospatial working memory in patients with acute stroke without severe cognitive impairment

Abstract: In a stressful context, the contribution of state anxiety to reduced working memory performance is more pronounced in patients with acute stroke than in controls. These results are of particular relevance for clinicians assessing patients in the acute phase of stroke in which anxiety is highly prevalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…Reported anxiety was not associated with change in cognitive performance. This finding is in contrast to prior studies investigating a stroke population [46] and in healthy individuals [47]. Both of these studies found that anxiety had a detrimental impact on cognitive functions.…”
Section: Discussioncontrasting
confidence: 99%
“…Reported anxiety was not associated with change in cognitive performance. This finding is in contrast to prior studies investigating a stroke population [46] and in healthy individuals [47]. Both of these studies found that anxiety had a detrimental impact on cognitive functions.…”
Section: Discussioncontrasting
confidence: 99%
“…This relationship between depressive symptoms and poorer cognitive function was also found in patients with minor stroke who have relatively good general outcomes and a promising long-term prognosis (Morsund et al, 2019). The association between anxiety and performance-based cognitive function seems to be less clear, and contradictory findings exist (Grosdemange et al, 2015;Morsund et al, 2019). In studies using self-report measures of cognitive function, higher levels of self-reported cognitive difficulties are commonly related to higher levels of depression post-stroke (van Rijsbergen et al, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…Anxiety is always accompanied by changes in cognitive processing, and the effects of anxiety on cognitive performance may be mediated by their effects on WM (Eysenck and Calvo, 1992;Owens et al, 2014). Increasing evidence indicates that the performance of anxious individuals is more easily impaired by threat-related interference than is that of individuals without anxiety (Grosdemange et al, 2015). Anxiety is also associated with inactivity of the neural circuit involved in cognitive control (Sari et al, 2016), which has been described as a defect in cognitive control.…”
Section: Emotional Interference and Wm In Anxietymentioning
confidence: 99%